INOVASI PEMBELAJARAN HAFALAN DOA DENGAN BERMAIN PERAN SEBAGAI MODEL KURIKULUM TRANSISI TK-SD - Trisna, Dewi Sri Hening; Gularso, Dhiniaty; Cholimah, Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study develops an innovative prayer memorization learning approach through role-play as a transitional curriculum model from kindergarten to primary school at TK Islam Duta Ananda. The need for religious learning emphasizing meaningful understanding, emotional engagement, and children's transition readiness forms the rationale. Using Classroom Action Research (CAR) with cyclical stages across two cycles, involving 20 TK-B children, data were collected through observation, documentation, and parental involvement reports. Results demonstrate role-play-based prayer learning significantly improved memorization quality (from 35% to 85% achieving criteria), active participation, self-confidence, and independence in leading prayers. This model effectively aligns with transitional curriculum principles and may serve as a reference for early childhood education institutions.